Pengaruh Hidrogel Ekstrak Daun Binahong (Anredera Cordifolia(Ten.) Stennis) Terhadap Penyembuhan Luka Insisi pada Tikus Wistar - Muhammad Hafizh Hilmi; Eko Krisnarto; Afiana Rohmani (Lembaga Pengembangan Kinerja Dosen, 2025)
Background. The paradigm of treatment using herbal plants is still attached to the Indonesian people for wound healing. One of the plants that is often used for treatment and has the effect of accelerating wound, is the binahong plant (Anredera cordifolia). The aim of this study is to determine the effect of hydrogel of binahong leaf extract (Anredera Cordifolia(Ten.) Stennis) on the healing of incisional wounds in wistar rats. Method. This study uses a True Experimental research design with the Post Test Only Control Group Design method. The samples were 30 wistar Rattus norvegicus rats, divided into 5 groups, namely: K (control group), P1 (was given 10% puvidone iodine ointment), P2 (was given 5% binahong leaf extract hydrogel), P3 (was given 10% binahong leaf extract hydrogel), P4 (was given 20% binahong leaf extract hydrogel). The treatment was carried out for 14 days. Wound examination was carried out on days 1,3,6,9,12,14. The REEDA score parameter were used to assess wound healing. Result. The bivariate analysis using the Wilcoxon paired difference test in each experimental group showed a significant difference only in group P2 (was given 5% binahong leaf extract hydrogel) with group K (control group), group P1 (was given 10% puvidone iodine ointment) and group P2 (was given 5% binahong leaf extract hydrogel) during days 12 and 14. incision wound compared to groups P3 and P4 on the same day. The average score of the REEDA scale on days 1,3,6,9,12, and 14, the most significant incisional wound healing in wistar rats was given hydrogel binahong leaf extract with a concentration of 5%. Conclusion. There is an effectiveness of healing incision wounds in wistar rats by giving hydrogel binahong leaf extract. The hydrogel binahong leaf extract 5% is the most significant concentration assessed from the average REEDA scale score.